Strength and physiological characteristics of NCAA Division III American football players - Schmidt, W. D. (The Journal of Strength and Conditioning Research, 1999)
The purpose of this study was to examine strength and physiological parameters in 78 American football players who reported for the 1994 and 1995 preseason football training camp at a National Collegiate Athletic Association (NCAA) Division III college. The athletes were each tested one time for explosive power, upper-body strength, lower-body strength, muscular endurance, speed endurance, lower-body flexibility, and body composition. The performance data were analyzed according to position and playing status (starter vs. nonstarter). Significant (p 0.05) differences were observed between positions for all but the sit and reach test. For measures of muscular and speed endurance and lower-body explosive power, defensive backs scored the highest, whereas for measures of upper- and lower-body strength and upper-body explosive power, defensive linemen scored the highest. Starters performed significantly better than nonstarters for the seated medicine ball put, bench press, and hip sled. Further investigation that includes more NCAA Division III players from different institutions and regions is still warranted.